A Global Health Law Trilogy: Transformational Reforms to Strengthen Pandemic Prevention, Preparedness, and Response. Issue 3 (2022) - Meier, Benjamin Mason; Habibi, Roojin; Gostin, Lawrence O.
Abstract: This is a pivotal moment in the global governance response to pandemic threats, with crucial global health law reforms being undertaken simultaneously in the coming years: the revision of the International Health Regulations, the implementation of the GHSA Legal Preparedness Action Package, and the negotiation of a new Pandemic Treaty. Rather than looking at these reforms in isolation, it will be necessary to examine how they fit together, considering: how these reforms can complement each other to support pandemic prevention, preparedness, and response; what financing mechanisms are necessary to ensure sustainable health governance; and why vital norms of equity, social justice, and human rights must underpin this new global health system.